2010
DOI: 10.1264/jsme2.me10117
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR Detection of Host-Mediated Cyanophage Gene Transcripts during Infection of a Natural Microcystis aeruginosa Population

Abstract: The aim of this study was to develop a quantitative real-time reverse transcription-PCR (real-time RT-PCR) assay to detect and quantify mRNA of cyanophages within infected Microcystis aeruginosa cells in a freshwater pond. Laboratory-based data showed that the relative abundance of the cyanophage g91 mRNA within host cells increased before cyanophage numbers increased in culture. This transcriptional pattern indicated the kinetics of the viral infection suggesting the real-time RT-PCR method to be a potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
34
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 33 publications
6
34
1
Order By: Relevance
“…To quantify abundances of total M. aeruginosa, a real-time PCR assay was performed using primers 188F and 254R, which are based on sequences of the phycocyanin intergenic spacer (PC-IGS) gene, as described previously (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify abundances of total M. aeruginosa, a real-time PCR assay was performed using primers 188F and 254R, which are based on sequences of the phycocyanin intergenic spacer (PC-IGS) gene, as described previously (18).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the predicted genes in its genome have no detectable homologues in the existing databases, and thus, Ma-LMM01 was assigned as a member of a new lineage in the family Myoviridae (14,15). Since no strain closely related to Ma-LMM01 has been isolated, the degenerate primer set was designed based on environmental sequences of Ma-LMM01 g91 (tail sheath gene), which is phylogenetically distinct from other phage genes and has been used as a genetic marker of this phage (16)(17)(18). Clonal analysis using this primer set reveals high sequence divergence that is derived from single point mutations in natural populations (16).…”
mentioning
confidence: 99%
“…Hirosawanoike Pond receives high nutrient input in relation to its volume due to its use for raising carp agriculturally. This results in eutrophication and cyanobacterial blooms from early summer to autumn every year (48). Samples of surface water were taken from a boat every 3 h over a period of 24 h on 15 to 16 September and on 21 to 22 October 2009 at a fixed point in the pond.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown M. aeruginosa to be genetically highly heterogeneous (44,51); M. aeruginosa populations also undergo temporal changes in genotypic composition (4,52,53). Previously we isolated a phage, Ma-LMM01, infecting M. aeruginosa (57) and observed the potential qualitative impact of the cyanophage and its relatives on natural M. aeruginosa populations (54,56). However, Ma-LMM01 has a narrow host range despite the large genetic diversity of hosts, suggesting that there is a greater diversity of host-cyanophage combinations other than Ma-LMM01 and its host strain in natural M. aeruginosa populations (57).…”
mentioning
confidence: 98%